HEMATOLOGICAL AND MOLECULAR STUDY OF TRYPANOSOMA EVANSI IN EXPERIMENTALLY INFECTION IN RABBITS - R. Khalid Ali,; I. Badr Falih, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
The lack of a sensitive diagnostic test for trypanosomasis in animals may hamper epidemiological data and control program implementation. This study aimed to detection of Trypanosoma evansi in rabbits that experimentally infected by this parasite which identified from camels of iraq by polymerase chain reaction. A study was conducted on 24 males rabbit divided into two groups (12 rabbits for each group). The first group was injected intra peritoneal (i/p) with 0.5 ml containing 1x105 trypanosome. The second group injected with distilled water and considered as control. At 7 and 10 days post infection, blood sample were collected from these rabbits. White blood cells count was conducted after 14 and 28 days post infection. The results showed that the 18S RNA and RoTat 1.2 genes related to T. evansi were identified .Furthermore ,there was significant elevation of Neutrophils ,Monocytes ,Lymphocytes ,Eosinophil and Basophils in infected rabbits compared with the control group. From this study we can conclude that PCR is a sensitive and effective technique for diagnosis of T.evansi through using 18S RNA and RoTat 1.2 genes. In addition ,WBC count was significantly elevated in an infected rabbits compared to the control. Whereas ,Lymphocyte was significantly higher in control group compared with infected group.